On the Dynamics of Prey-Predator Model Involving Treatment and Infections Disease in Prey Population - Faisal Ali, Nidhal; Amer Aaid, Asraa (Iraqi Journal of Science, 2023)
In this paper, a mathematical model consisting of the prey- predator model with treatment and disease infection in prey population is proposed and analyzed. The existence, uniqueness and boundedness of the solution are discussed. The stability analyses of all possible equilibrium points are studied. Numerical simulation is carried out to investigate the global dynamical behavior of the system.